2017
DOI: 10.1136/bmjopen-2016-013901
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of the Cytosponge procedure for detecting Barrett's oesophagus: a qualitative study

Abstract: ObjectiveTo investigate the acceptability of the Cytosponge, a novel sampling device to detect Barrett's oesophagus (BE), a precursor to oesophageal adenocarcinoma (EAC), among people with risk factors for this condition.DesignA qualitative study using semistructured interviews and focus group discussions. Data were explored by three researchers using thematic analysis.SettingCommunity setting in London, UK.ParticipantsA recruitment company identified 33 adults (17 men, 16 women) aged 50–69 years with gastro-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 23 publications
1
41
0
4
Order By: Relevance
“…Our review showed that of 2,672 Cytosponge ® procedures there were only two SAE that could be directly attributed to the device (<1: 2,000) and both resolved without any ill-effects for the patient. The detachment is the most concerning risk factor to both clinicians and patients 28 . However, a retained sponge in the stomach would not be expected to cause any symptoms as was the case in the patient reported here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review showed that of 2,672 Cytosponge ® procedures there were only two SAE that could be directly attributed to the device (<1: 2,000) and both resolved without any ill-effects for the patient. The detachment is the most concerning risk factor to both clinicians and patients 28 . However, a retained sponge in the stomach would not be expected to cause any symptoms as was the case in the patient reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Previous interview-based, quality study on 33 participants with GERD showed that Cytosponge ® is acceptable for most participants, as well as being preferred to endoscopy 28 . In our study, most patients (79.3%) scored their experience as at least “neutral” (VAS≥5) and the median VAS score was 6.0 (IQR 5.0–8.0).…”
Section: Discussionmentioning
confidence: 99%
“…Die Verwendung der Abrasiv-Zytologie als Screening-Verfahren auf BE und EAC ist dagegen eine relativ neue Methode (▶ Abb. 3) [54].…”
Section: Erweiterte Auswertung Von Biopsien Auf Biomarker Für Intraepunclassified
“…Die Ergebnisse dieser Studie werden erstmals Evidenz zu der Frage erbringen, ob mit diesem einfachen, billigen sowie anwender-und patientenfreundlichen Verfahren ein effektives Screening auf Barrett-Ösophagus betrieben werden kann und die sich ggf. anschließende Surveillance tatsächlich in der Lage ist, das Outcome (tumorassoziierte und Gesamtmortalität) signifikant zu verbessern [54]. Speziell zur risikoadaptierten Surveillance beim Barrett-Ösophagus wird zusätzlich eine weitere britische prospektive, randomisierte und populationsbasierte Studie Antworten liefern (BOSS-Trial) [60].…”
Section: Erweiterte Auswertung Von Biopsien Auf Biomarker Für Intraepunclassified
“…Die Ergebnisse dieser Studie werden erstmals Evidenz zu der Frage erbringen, ob mit diesem einfachen, billigen sowie anwender-und patientenfreundlichen Verfahren ein effektives Screening auf Barrett-Ösophagus betrieben werden kann und die sich ggf. anschließende Surveillance tatsächlich in der Lage ist, das Outcome (tumorassoziierte und Gesamt-Mortalität) signifikant zu verbessern [54]. Speziell zur risiko-adaptierten Surveillance beim Barrett-Ösophagus wird zusätzlich eine weitere britische prospektive, randomisierte und populationsbasierte Studie Antworten liefern (BOSS-Trial) [60].…”
Section: Erweiterte Auswertung Von Biopsien Auf Biomarker Für Intraepunclassified